Multilingualism of Tourism Attraction in Bandung - Danuwijaya, Ari Arifin; Abdullah, Cep Ubad (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2021)
This study aims to identify programs that have been carried out by managers of tourist attractions in the North Bandung area. This study uses a qualitative approach, primary data obtained through observations and interviews. Secondary data is obtained through previous research, local government policies, and digital media through websites and social media. The method of analysis uses qualitative descriptive analysis through the stages of analysis before being in the field, data reduction, data presentation, and conclusion drawing. The results showed that the tourist attractions of Tebing Keraton and TWA Tangkubanparahu have multi-language communication through online and offline media.